Floods and spillovers: households after the 2011 great flood in Thailand - Ilan Noy; Cuong Nguyen; Pooja Patel (Center for Economic Studies and ifo Institute (CESifo), 2019)
In 2011, Thailand experienced its worst flood ever. Using repeated waves of the Thai Household Survey, we analyse the flood's economic impacts. In 2012, households answered a set of questions on the extent of flooding they experienced. We use this self-identified flood exposure, and external exposure indicators from satellite images, to identify both directly affected households and those that were not directly flooded but their communities were (the spillovers). We measure the impact of the disaster on income, expenditure, assets, debt and savings levels, directly, and indirectly on spillover households. We also analyse the flood's impacts across different socio-economic groups.
Keywords: O12; Q54; 330; disaster; flood; Thailand; economic impact